Prevalence and socio-demographic factors associated with physical inactivity among primary health care users in Tirana, Albania: A cross-sectional study (Journal of Health Sciences, 2021)
Introduction: The World Health Organization (WHO) defines physical activity (PA) as any movement of the body produced by skeletal muscle that requires expenditure of energy. The aim of research is to assess the prevalence of and socio-demographic characteristics associated with physical inactivity (PI) among adult primary healthcare (PHC) users in Tirana, the capital of Albania.Methods: This was a cross-sectional study carried out in Tirana from November 2020 to January 2021. During this period 500 consecutively approached individuals aged ≥18 years exiting PHC centers were interviewed face-to-face about the presence of some of the risk factors for non-communicable disease. A structured WHO STEPS questionnaire, an integrated part of which is the instrument required for this study, “Global PA Questionnaire,” was used. In addition to demographic and socioeconomic data, we obtained data on the performance of PA in terms of domains, duration, and intensity. Logistic regression was used to assess socio-demographic factors associated with PI.Results: Prevalence of PI in the study population was 31.6%. Following multivariable adjustment for all covariates, significant positive correlates of PI were female gender, rural residence, retiree status, and unemployment. Conversely, there was an inverse association with moderate level of education.Conclusions: Similar to that of other European populations, the population of Tirana has a high rate of PI showing an upward tendency. The population groups at the highest risk of PI who may be targeted for intervention programs to address this risk factor are women, rural residents, unemployed persons, and retirees.